Apolipoprotein M expression modifies the sphingolipid landscape in murine blood and lymph - Blaho, Victoria A.; Minyard, Joshua T. (Frontiers in Immunology, 2025)
Members of the diverse family of sphingolipids (SPL), such as ceramides (Cer) and sphingomyelins (SM), are well-known structural and bioactive signaling molecules. A key SPL family member and critical signaling lipid, sphingosine 1-phosphate (S1P), is carried in blood primarily by its “chaperone” protein apolipoprotein M (ApoM) on high-density lipoprotein (HDL) particles. S1P has been shown to regulate diverse biological pathways through specific G protein-coupled receptor signaling (GPCR) that can be modulated based upon chaperone: ApoM or albumin. Blood concentrations of ApoM itself are altered in human diseases such as coronary artery disease, type I and II diabetes, and systemic lupus erythematosus, diseases that have also been linked to changes in other SPL species; however, studies measuring molecules only in blood while neglecting lymph concentrations may be excluding clues to the physiology affected by multiorgan metabolic pathways. Comparing SM, dihydroSM, Cer, dihydroCer, α-hydroxy Cer (αOHCer), Cer 1-phosphate (C1P), sphingosine (Sph)/dihydroSph, S1P/dihydroS1P, and diacylglycerol (DAG) concentrations in wild-type mouse blood and lymph plasmas with those in mice lacking ApoM and mice expressing a human transgene of ApoM, we describe unanticipated differences between the blood and lymph sphingolipidomes and their ApoM-responsive lipid species. Of the 100 unique SPL species targeted, 97 were identified in blood and 94 in lymph. Some of the most striking findings were in lymph, where we identified αOHCer as a previously unidentified major SPL constituent. This report provides a unique resource and starting point for further investigations into the contributions of the circulating sphingolipidome to homeostasis and disease.